Long Coronavirus Disease Symptoms and their Association with Different Risk Factors - Rasha A. F. Jasim (Medical Journal of Babylon)
Background: Although there are some studies trying to detect various long or post coronavirus disease (COVID-19) symptoms and some risk factors, long COVID-19 symptoms and their association with some possible risk factors such as age, sex, blood group, and oxygen level are still not well understood and required more studies worldwide. Objective: Therefore, this study included 206 patients. My questionary has different questions for the participants such as the type of symptoms they had post COVID-19 infection, to determine the most prevalence long symptoms. Materials and Methods: Moreover, to determine the association of post-acute sequelae of COVID-19 with some risk factors, the questionnaire included questions about the participant’s age, gender, blood group, and oxygen rate during the infection. Results: My results showed that fatigue and muscle pain are the most prevalent long or post COVID-19 symptoms followed by forgetfulness and depression, chest pain and cough, loss of smell and taste, diarrhea, and abdominal pain. Also the results found that female patents, and persons with age from 19 to 29, as well as positive Rh blood group except AB+ are more susceptible to long symptoms. Moreover, the results showed that there is an association between oxygen rate reduction and the long COVID-19 symptoms. Conclusion: Some corona virus patients develop post disease symptoms, and it looks like that variable factors influence that. So understanding the correlation between appearance of the long COVID-symptoms and these the risk factors presents valuable insights, the conclusions warrant justification through larger clinical trials.